Student recruitment and relationship marketing – convergence or contortion? - Beneke, J (South African Journal of Higher Education, 2011)
This article investigates the intersection of student recruitment and relationship marketing in the public high education sector. They key objectives of this analysis are to understand if a strategic fit exists and whether South African institutions are indeed embracing the principles of relationship marketing in order to optimise their student recruitment programmes. Whilst the merits of building and developing student relationships over an extended timeframe are well documented in scholarly literature, the situation on the ground suggests that local institutions remain somewhat conservative in this respect. Despite success stories from a select number of private colleges, local institutions have tended to persist with tried-and-trusted recruitment techniques due to the logistical and inancial resources in implementing a relationship-oriented strategy. In this respect, mass marketing and direct marketing techniques remain the order of the day, although relationship marketing is seen as a future platform should intensified competition necessitate a fundamental change in approach.